A Matter of Choices : Memoirs of a Female Physicist - Ajzenberg-Selove, Fay, 1926- (Book collections on Project MUSE., 1994)
When the author became a nuclear physicist, the number of women in the field could be counted on one hand. In this memoir, she reveals her difficult journey to international recognition in physics. She is frank about the ways being a woman has made a difference in her opportunities and choices as a scientist--and how, by being a woman, she has made a difference in the world of physics.